Physiotherapy clinical considerations in the prescription of ankle-foot orthoses in post-stroke patients - Klever Armando Bonilla Yacelga, Jorge Gabriel Maldonado Cornejo Samuel Olegario Iñiguez Jiménez (Journal of International Crisis and Risk Communication Research, 2024)
Introduction: Cerebrovascular accident (CVA) is one of the main causes of deterioration of motor function, the prescription of ankle-foot orthoses (AFO) has systemic effects on joint movement to optimize walking. Objective:To analyze based on current scientific evidence, the main clinical considerations in physiotherapy for the prescription of ankle and foot orthoses in patients with sequelae of stroke. Development: There are different types of ankle-foot orthoses, among the most used are: rigid, dynamic, and articulated AFO, each with its respective characteristics. A comprehensive evaluation of strength, balance, muscle tone, reflexes, sensation, gait, and functionality should be performed. When using AFO, the duration of use and care should also be considered, especially when it comes to skin care. Over time, it is necessary to established to promote the patient's function in activities of daily living (ADL). Conclusions: The use of AFO in post-stroke patients depends on various aspects such as muscle strength, muscle tone and degree of joint instability. It is essential to consider the type of orthosis to be prescribed, whether rigid, dynamic, or articulated; The state of sensitivity and musculoskeletal difficulties will guide the choice of the material to use. Based on these criteria and the evaluation carried out by the physiotherapist, the most appropriate orthosis will be prescribed to allow safe and effective walking.